Production and Characterization of Biofuel from Non-Edible Oils: An Alternative Energy Sources to Petrol Diesel - Abdulkareem, A.S.; Jimoh, A.; Afolabi, A.S.; Odigure, J.O.; Patience, D. (IntechOpen, 2012)
None